(untitled) (Research, Society and Development, 2022)
Objective: to analyze the impact of the COVID-19 pandemic on cancer diagnosis in the periods from 2019 to 2021. Methodology: this is a cross-sectional and descriptive study, data collection was carried out through the DATASUS TABNET application in the period 2019, pre-pandemic year and in the 2020-2021 biennium. Results: A reduction in the number of cases of cancer diagnoses was observed in the years 2020 and 2021 when compared to the year 2019. When staging, most diagnoses with filled fields occurred in stage III in all years analyzed. Regarding the primary site of the neoplasm, in the three years analyzed, the highest number of diagnoses was breast cancer, followed by non-melanoma skin cancer and cancer in connective tissue and other soft tissues in all years. Regarding the time between diagnosis and initiation of treatment, in the years 2019 and 2020 the majority occurred after 60 days of diagnosis. The year 2021 saw a decrease in the start of treatment for patients starting within 30 days of cancer diagnosis. Conclusion: A significant relationship was observed between the COVID 19 pandemic and the reduction of cancer diagnoses in Paraíba in the years 2020 and 2021.